Maxims Flouting In Home Alone 2 - Yeuyanan, Stefanus Ronaldo (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This research study is a present research study that aims to find the maxims that are flouted in the Home alone 2 movie. There are two purposes of this study, namely to find what types of maxim that is flouted by the character in the movie, and what are the reasons for the characters to flout the maxim. This study takes the four maxims theory that was proposed by Paul Grice (1975) with the aim of analyzing the data. This study uses the theory that consist of Transcribing data, Pre-coding data and Coding data, and Growing ideas, that was proposed by Zoltan Dörnyei (2007) in order to do the method of collecting data and the analyzing data. Concerning the theory, the data is transcribed from the oral form into textual form. In the pre-coding section, the data that has been transcribed is indicated to the types of flouting maxim. Then, in the coding section, the data is divided into groups of maxims. Lastly, there are explanations are made to describe how the maxims are flouted and the reasons for the characters to flout them. The findings and discussion shows that all four maxims, namely maxim of quantity, maxim of quality, maxim of manner and maxim of relation are flouted by the characters. The maxim of quality is mostly flouted, with 11 times flouted. The reasons to flout this maxim are lying, mocking, and refusing. The maxim of quantity is flouted nine times. The reasons to flout this maxim are informing, intimidating, forcing, worrying, satisfying, and forgetfulness. The maxim of manner is flouted seven times. The reasons behind flouting the maxim of manner are feeling guilty, leading the interlocutor to guess something, and rejecting other opinion. Lastly, the maxim of relation is flouted three time. The reasons consist of joking and expressing worries. Keywords: Flouting maxim, Implied meaning, Utterance, Home Alone 2 movie